2016
DOI: 10.1007/s13224-016-0842-x
|View full text |Cite
|
Sign up to set email alerts
|

Carboprost Versus Oxytocin for Active Management of Third Stage of Labor: A Prospective Randomized Control Study

Abstract: Background and Objectives Postpartum hemorrhage is the single largest and leading cause of maternal morbidity and mortality not only in developing countries but also in developed countries. The present study is an attempt to evaluate the scope of using prophylactic intramuscular carboprost tromethamine 125 lg in comparison with intramuscular oxytocin 10 units for the active management of third stage of labor. Materials and Methods Two hundred pregnant women at term with spontaneous onset of labor were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…Sensitivity analysis by excluding a dose of 125 ug carbetocin trial 15 showed that the results were not substantial influenced, and they were just slight changes. Funnel plots and Begger's and Egger's tests found no significant publication bias.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Sensitivity analysis by excluding a dose of 125 ug carbetocin trial 15 showed that the results were not substantial influenced, and they were just slight changes. Funnel plots and Begger's and Egger's tests found no significant publication bias.…”
Section: Resultsmentioning
confidence: 95%
“…Except for Sunil Kumar KS’s article (125 ug), 15 all articles performed a standard dose of 100 ug carbetocin. The articles were conducted in various countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carboprost can cause significant bronchospasm, even in patients without asthma . Other effects include hypertension, diarrhoea, nausea, vomiting, flushing, hyperpyrexia and myalgia . Sulprostone may cause fever, diarrhoea and painful uterine contraction .…”
Section: Other Uterotonic Agentsmentioning
confidence: 99%
“…Generally, activation of EP1 and EP3 receptors is associated with an excitatory response, whereas EP2 and EP4 are associated with inhibition of smooth muscle contractility ( Woodward et al, 2011 ). Furthermore, clinical uses of the prostaglandin E 2 agonist dinoprostone, include the stimulation of uterine smooth muscle contractions during labor ( Stephenson and Wing, 2015 ) with the prostaglandin F 2α agonist, carboprost, being a viable alternative to oxytocin during the management of labor ( Sunil Kumar et al, 2016 ). Therefore, the involvement of EP1, EP3 and FP receptors is of particular interest in the modulation of lower urinary tract contractility due to their excitatory effect when stimulated.…”
Section: Introductionmentioning
confidence: 99%